‘Earth system engineers’ and the cumulative impact of organisms in deep time - Simon A.F. Darroch; Michelle M. Casey; Alison T. Cribb; Amanda E. Bates; Matthew E. Clapham; Dori L. Contreras; Matthew Craffey; Ivo A.P. Duijnstee; William Gearty; Nicholas J. Gotelli; Marcus J. Hamilton; Riley F. Hayes; et al. (Trends in Ecology & Evolution, 2025)

Food wastes for bioproduct production and potential strategies for high feedstock variability - Phavit Wongsirichot; Benjamin Barroso-Ingham; Alexander Hamilton; Mariana Parroquin Gonzalez; Roger Romero Jimenez; Robin Hoeven; James Winterburn (Waste Management, 2024)

Modeling coupled dynamics of an empirical predator-prey system to predict top predator recovery - Samantha N.M. Hamilton; M. Tim Tinker; Joseph Jackson; Joseph A. Tomoleoni; Michael C. Kenner; Julie L. Yee; Tom W. Bell; Max C.N. Castorani; Benjamin H. Becker; Brent B. Hughes (Biological Conservation, 2024)

Participation in collaborative fisheries research improves the perceptions of recreational anglers towards marine protected areas - Erin M. Johnston; Grant T. Waltz; Rosamaria Kosaka; Ellie M. Brauer; Shelby L. Ziegler; Erica T. Jarvis Mason; Hunter S. Glanz; Lauren Zaragoza; Allison N. Kellum; Rachel O. Brooks; Brice X. Semmens; Christopher J. Honeyman; et al. (Frontiers in Marine Science, 2024)
Collaborative fisheries research programs engage stakeholders in data collection efforts, often with the benefit of increasing transparency about the status and management of natural resources. These programs are particularly important in marine systems, where management of recreational and commercial fisheries have historically been contentious. One such program is the California Collaborative Fisheries Research Program (CCFRP), which was designed in 2006 to engage recreational anglers in the scientific process and evaluate the efficacy of California’s network of marine protected areas. CCFRP began on the Central Coast of California and expanded statewide in 2017 to include six partner institutions in three regions: Northern, Central, and Southern California. To date, over 2,000 volunteer anglers have participated in the program, with many anglers volunteering for multiple years. However, the impacts of outreach, education, and collaborative research on those anglers at the statewide scale are currently unknown. Thus, the objective of the current study was to survey the statewide pool of volunteer anglers to assess the degree to which participation in CCFRP has influenced angler perceptions of MPAs, fisheries management, and conservation. We received 259 completed surveys out of a pool of 1,386 active anglers, equating to an 18.7% response rate. Participation in CCFRP resulted in a significant, positive impact on anglers’ attitudes towards MPAs in California across all regions. Anglers who participated in six or more CCFRP fishing trips had a more positive perception of MPAs than those who participated in fewer trips. Volunteer anglers across all regions perceived that they caught larger fishes, a higher abundance of fishes, and a greater diversity of species inside MPAs, consistent with the ecological findings of the program. These results highlight the benefits of involving community members in collaborative scientific research. Collaboration between researchers and the broader community increases transparency and trust between stakeholders, and results in greater understanding of natural resource dynamics, ultimately producing better management outcomes.

Combustion conditions influence toxicity of flame-generated soot to ocular (ARPE-19) cells. - Dhruv Mitroo; Durgesh N. Das; Paul D. Hamilton; Benjamin M. Kumfer; Nathan Ravi (Environmental Pollution, 2024)

Increasing Skin Cancer Prevention in Young Adults: the Cumulative Impact of Personalized UV Photography and MC1R Genetic Testing - Yelena P. Wu; Jada G. Hamilton; Kimberly A. Kaphingst; Jakob D. Jensen; Wendy Kohlmann; Bridget G. Parsons; Helen M. Lillie; Xuechen Wang; Benjamin Haaland; Ali P. Wankier; Douglas Grossman; Jennifer L. Hay (Journal of Cancer Education, 2023)

Benefits and Challenges of a Stakeholder-Driven Shellfish Toxicity Forecast in Coastal Maine - Nicholas R. Record; Johnathan Evanilla; Kohl Kanwit; Craig Burnell; Carmen Cartisano; Bryant J. Lewis; Jill MacLeod; Benjamin Tupper; David W. Miller; Adrienne T. Tracy; Carol White; Matt Moretti; et al. (Frontiers in Marine Science, 2022)
Paralytic shellfish poison (PSP) is a human health concern for shellfish aquaculture and wild harvest. This paper discusses lessons learned from a forecasting program for PSP in coastal Maine, USA, designed based on stakeholder input, and run in an operational mode for the 2021 season. The forecast uses a deep learning algorithm to make site-specific, probabilistic forecasts at a weekly forecast range for toxin levels measured in shellfish tissue. Forecasts had high accuracy in the 2021 season, correctly predicting closure events and locations despite a highly unusual season. Stakeholders reported a positive view of the forecast system, and stakeholder input continues to be of key importance as further modifications are made to the system. There are benefits and challenges to the stakeholder-based design of the system.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Sex differences in changes of protein synthesis with rapamycin treatment are minimized when metformin is added to rapamycin - Christopher A. Wolff; Marcus M. Lawrence; Hunter Porter; Qian Zhang; Justin J. Reid; Jaime L. Laurin; Robert V. Musci; Melissa A. Linden; Frederick F. Peelor; Jonathan D. Wren; Joseph S. Creery; Kyle J. Cutler; et al. (GeroScience, 2021)

Development of community of practice to support quantitative risk assessment for synthetic biology products: contaminant bioremediation and invasive carp control as cases - Benjamin D. Trump; Christy Foran; Taylor Rycroft; Matthew D. Wood; Nirzwan Bandolin; Mariana Cains; Timothy Cary; Fiona Crocker; Nicholas A. Friedenberg; Patrick Gurian; Kerry Hamilton; Jan Jeffrey Hoover; et al. (Environment Systems and Decisions, 2018)

Global species delimitation and phylogeography of the circumtropical ‘sexy shrimp’ Thor amboinensis reveals a cryptic species complex and secondary contact in the Indo‐West Pacific - Benjamin M. Titus; Marymegan Daly; Natalie Hamilton; Michael L. Berumen; J. Antonio Baeza (Journal of Biogeography, 2018)
Aim The “sexy shrimp” Thor amboinensis is currently considered a single circumtropical species. However, the tropical oceans are partitioned by hard and soft barriers to dispersal, providing ample opportunity for allopatric speciation. Herein, we test the null hypothesis that T. amboinensis is a single global species, reconstruct its global biogeographical history, and comment on population‐level patterns throughout the Tropical Western Atlantic. Location Coral reefs in all tropical oceans. Methods Specimens of Thor amboinensis were obtained through field collection and museum holdings. We used one mitochondrial ( COI ) and two nuclear (NaK, enolase) gene fragments for global species delimitation and phylogenetic analyses ( n = 83 individuals, 30 sample localities), while phylogeographical reconstruction in the TWA was based on COI only ( n = 303 individuals, 10 sample localities). Results We found evidence for at least five cryptic lineages (9%–22% COI pairwise sequence divergence): four in the Indo‐West Pacific and one in the Tropical Western Atlantic. Phylogenetic reconstruction revealed that endemic lineages from Japan and the South Central Pacific are more closely related to the Tropical Western Atlantic lineage than to a co‐occurring lineage that is widespread throughout the Indo‐West Pacific. Concatenated and species tree phylogenetic analyses differ in the placement of an endemic Red Sea lineage and suggest alternate dispersal pathways into the Atlantic. Phylogeographical reconstruction throughout the Tropical Western Atlantic reveals little genetic structure over more than 3,000 km. Main conclusions Thor amboinensis is a species complex that has undergone a series of allopatric speciation events and whose members are in secondary contact in the Indo‐West Pacific. Nuclear‐ and mitochondrial‐ gene phylogenies show evidence of introgression between lineages inferred to have been separated more than 20 Ma. Phylogenetic discordance between multi‐locus analyses suggest that T. amboinensis originated in the Tethys sea and dispersed into the Atlantic and Indo‐West Pacific through the Tethys seaway or, alternatively, originated in the Indo‐West Pacific and dispersed into the Atlantic around South Africa. Population‐level patterns in the Caribbean indicate extensive gene flow across the region.

Targeting mitochondrial function and proteostasis to mitigate dynapenia - Robert V. Musci; Karyn L. Hamilton; Benjamin F. Miller (European Journal of Applied Physiology, 2018)

Influence of Nrf2 activators on subcellular skeletal muscle protein and DNA synthesis rates after 6 weeks of milk protein feeding in older adults - Adam R. Konopka; Jaime L. Laurin; Robert V. Musci; Christopher A. Wolff; Justin J. Reid; Laurie M. Biela; Qian Zhang; Fredrick F. Peelor; Christopher L. Melby; Karyn L. Hamilton; Benjamin F. Miller (GeroScience, 2017)

The capacity of biochar made from common reeds to neutralise pH and remove dissolved metals in acid drainage - Luke M. Mosley; Philip Willson; Benjamin Hamilton; Greg Butler; Russell Seaman (Environmental Science and Pollution Research, 2015)